CITATION ANALYSIS OF COMPUTERS, CONTROL SYSTEMS AND INFORMATICS RESEARCHES IN A SINGLE SCIENTIFIC JOURNAL - Natakusumah, Engkos (BACA: Jurnal Dokumentasi dan Informasi, 2016)
The problems of producing high quality scientific articles are not only using very poor sources of new literature as references, but also difficulties in determining the position of the research. Consequently the existence of research position in the scientific world becomes not clear. This paper explored the answer to those problems statement above using citation analysis method to 93 articles in a scientific journal. The journal used for this research is Journal “Inkom”, covering scientific articles of informatics, computer, and control system, from 2007 to 2012, produced by The Research Center for Informatics Indonesian Institute of Sciences. The aims of this research are: (1) to study the most cited authors; (2) to study the most cited bibliographic resources; (3) to study the most cited subjects. In order to achieve those aims, this research uses method of quantitative approach through bibliometrics analysis to study article characteristics using citation analysis. The results from 667 cited articles showed that: (1) the most cited authors is Malvino. Whereas three other most frequent cited authors are Elan, Murni, and Rivest; (2) kind of the most cited literature is book, 48.87%, followed by cited literature from internet 18.44% and from journals 16,19%; (3) the average of cited literature perarticle is 7; and (4) the most cited subjects is electronics. The results of citation analysis showed that there are increasing quality of scientific articles with clear research position, supported by appropriate literature sources. In 2012 there are 197 citations from 17 articles, the average of citation for one article is 11, this means that there are increasing numbers of using the citation compared to the year before. In general, the science coverage dominating citations in Journal “Inkom” are the subjects of electronics, sensors and algorithms. The result showed that there are dominating subjects citations related to the year of publications: 2007-2009 in computers (electronics), 2011 in control systems (sensors), and 2012 in informatics (algorithms).